2016
DOI: 10.3389/fnbeh.2016.00196
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Brinp2 or Brinp3, or Both, Exhibit Behaviors Consistent with Neurodevelopmental Disorders

Abstract: Background: Brinps 1–3, and Astrotactins (Astn) 1 and 2, are members of the Membrane Attack Complex/Perforin (MACPF) superfamily that are predominantly expressed in the mammalian brain during development. Genetic variation at the human BRINP2/ASTN1 and BRINP1/ASTN2 loci has been implicated in neurodevelopmental disorders. We, and others, have previously shown that Brinp1−/− mice exhibit behavior reminiscent of autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD).Method: We created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Indeed, our results agree with numerous studies demonstrating the association between mood instability and neuroticism, which is reassuring, given that mood instability has been described as a "distinctive feature of neuroticism" [46]. Prior studies have implicated this locus in determining psychiatric traits [44,45,47,48] which overlap to varying degrees with these intermediate traits, providing additional weight to the hypothesis that alterations in synaptic signalling could underpin many psychological and psychiatric phenotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, our results agree with numerous studies demonstrating the association between mood instability and neuroticism, which is reassuring, given that mood instability has been described as a "distinctive feature of neuroticism" [46]. Prior studies have implicated this locus in determining psychiatric traits [44,45,47,48] which overlap to varying degrees with these intermediate traits, providing additional weight to the hypothesis that alterations in synaptic signalling could underpin many psychological and psychiatric phenotypes.…”
Section: Discussionsupporting
confidence: 90%
“… 82 ) and validated to be present in MF synaptosomes. Brinp2 KO mice display hyperactivity 83 , but the function of BRINP2 is not known. Finally, the transmembrane protein IgSF8 interacts with tetraspanins and integrins 84 86 , and is thought to modulate cell motility in immune and cancer cells through tetraspanin microdomains 87 , 88 .…”
Section: Discussionmentioning
confidence: 99%
“…BRINP3 is another anxiety-associated gene identified by GEWIS. Berkowicz et al [41] observed that BRINP3−/− mice altered sociability and exhibited marked changes in anxietyresponse on the elevated plus maze.…”
Section: Discussionmentioning
confidence: 99%